The resource allocation process in the health sector in Zambia and issues of equity - Muloshi, Flora Chitalu (University of Cape Town, 2014)
Bibliography : leaves 102-109. === This research project was undertaken to identify the factors that are cons!dered in the formula for allocating resources in the health sector in Zambia as compared to those ones identified in international literature some of which are: population size, demographic composition of population, morbidity/mortality profile, and the socioeconomic status of population.